A new record of species Radermachera microcalyx C. Y. Wu & W. Yin (Bignoniaceae) for the flora of Vietnam - Phuong, Vu Xuan; Xuyen, Do Thi; Vu, Dang Quoc; Phe, Phung Van; Son, Dang Van (Academia Journal of Biology, 2012)
The genus Radermachera Zollinger & Morit compcises about 16 species, mainly distributed in tropical Asia, there are 7 Radermachera species in Vietnam. During the study of specimen and documents of Gesneriaceae of Vietnam, we found Radermachera microcalyx C. Y. Wu & W. Yin in Lao Cai province, North Vietnam. Radermachera microcalyx is tree, ca. 20 m tall. Leaves compound pinnately 1 times, ca. 40-60 cm long; leaflet 5-7 pairs, ovate or elliptic, ca. 11-26 × 4-6 cm, margin entire, lateral 6-10 pairs. Inflorescences thyrsus, terminal; calyx campanulate, 5 small teeth, apex truncate; corolla pale yellow, tube ca. 2-2,5 mm long; style filiform; capsule line, dehiscung by 2 valves; seeds many, minute. This species is closed to R. glandulosa but differs by having leaves dim glandular in abaxial, corolla tube 2.0-2.5 cm long, ca. 4-5 mm in diam. Voucher specimens were collected in Hoang Lien - Van Ban reserver, Lao Cai province and deposited in the Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN).